The Emergence of Ukraine Self-Determination, Occupation, and War in Ukraine, 1917-1922 - Dornik, Wolfram (Canadian Institute of Ukrainian Studies Press, 2015)
This book is a collection of essays by prominent historians from Austria, Germany, Ukraine, Poland and Russia, who undertook a thorough and detailed study of one as yet inadequately researched aspect of the First World War--the occupation of Ukraine by the Central Powers in 1918. The book provides a new and fresh perspective on the historical context of Ukraine's struggle for independence following the First World War.